Exploring the relationship between “other block-holders” and the performance of family-controlled corporations in Malaysia - Ng, Sin Huei (Emerald Group Publishing Limited, 2015)
Purpose – The purpose of this paper is to provide an exploration on how important are “other block-holders” in explaining the performance of family-controlled corporations in Malaysia. Three important groups of block-holders are identified for the purpose, namely the “foreign institutional investors”, the “domestic institutional investors” and the “government”. Design/methodology/approach – The sample was drawn based on the companies listed on the Main Board of Bursa Malaysia. All the relevant block-holders’ ownership data are hand-collected from the annual reports published by the listed corporations and descriptive statistics together with regression analysis are employed. Findings – Overall it is found that the presence of a second block-holder in family-controlled corporations leads to better performance compared to the corporations where the controlling families act as the sole block-holder. Moreover, this study finds that the identity of the block-holders with the extent of their ownership is important in explaining the performance. Specifically, “foreign institutional investors” and “government” are found to be significant in terms of the extent of their equity holdings and the performance of these corporations, respectively. Conversely, no such relationship is found in the equity holdings of “domestic institutional investors” and the corporation performance. Such finding may imply the possible limited ability and constraints faced by the “domestic institutional investors” in Malaysia to exert effective monitoring and pressure on the management for enhanced corporation performance. Originality/value – Many studies researched the influence of family ownership on the performance of family-controlled corporations but there are limited studies conducted on the influence of “other block-holders” in affecting the performance of these corporations. This paper is an attempt to provide an initial exploration on how important are these “other block-holders” in explaining the performance of these corporations in the context of a small emerging economy, Malaysia.